2006
DOI: 10.1002/sca.4950280501
|View full text |Cite
|
Sign up to set email alerts
|

The trajectories of secondary electrons in the scanning electron microscope

Abstract: Summary: Three-dimensional simulations of the trajectories of secondary electrons (SE) in the scanning electron microscope have been performed for plenty of real configurations of the specimen chamber, including all its basic components. The primary purpose was to evaluate the collection efficiency of the Everhart-Thornley detector of SE and to reveal fundamental rules for tailoring the set-ups in which efficient signal acquisition can be expected. Intuitive realizations about the easiness of attracting the SE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…If the collection efficiency (CE) is defined as the ratio of the number of SE1 plus SE2 collected by the E‐T SE detector to that emitted from the sample, then this hindering effect can be characterized. It has been reported that CE can reach as low as 0.05−0.2 for WD = 10 mm, indicating serious hindering effect at routine WD. Therefore, higher CE for SE1 plus SE2 is expected provided that this hindering effect can be diminished.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the collection efficiency (CE) is defined as the ratio of the number of SE1 plus SE2 collected by the E‐T SE detector to that emitted from the sample, then this hindering effect can be characterized. It has been reported that CE can reach as low as 0.05−0.2 for WD = 10 mm, indicating serious hindering effect at routine WD. Therefore, higher CE for SE1 plus SE2 is expected provided that this hindering effect can be diminished.…”
Section: Discussionmentioning
confidence: 99%
“…SE1 plus SE2 emitted from a sample are attracted and accelerated toward the side‐attached E‐T SE detector by the collector grid, which is generally positively biased with a +300 V voltage. However, acceleration of SE1 plus SE2 toward the detector could be hindered due to the presence of the pole piece, as illustrated in Figure a. If the collection efficiency (CE) is defined as the ratio of the number of SE1 plus SE2 collected by the E‐T SE detector to that emitted from the sample, then this hindering effect can be characterized.…”
Section: Discussionmentioning
confidence: 99%
“…The detector is usually side‐positioned in the specimen chamber, just below the objective lens (OL). Only weak electrostatic field attracts the low energy SEs (Konvalina & Müllerová, 2006) and nearly no magnetic field exists in the specimen region in the traditional configuration.…”
Section: Introductionmentioning
confidence: 99%
“…When a lateral detector is operated, the field effects pushing electrons emitted from a negative surface potential towards a positively biased grid may also lead to a possible increase of the apparent brightness of the pre-irradiated area. The collection efficiency of a lateral detector is normally very large so that the field amplification effect is expected to be less than for a coaxial detector but detailed calculations of trajectories are complicated because they involve working distance, z1, voltage drop between the detector's grid and the specimen surface as well as distance between the specimen and the detector [12]. For short working distances and large distances between the specimen and the grid, the SE trajectories would be mainly governed by the field between the specimen and the pole pieces and the amplification effect may be less than unity for the lateral detector to the advantage of electrons going towards the pole pieces.…”
Section: Article In Pressmentioning
confidence: 99%
“…Then this formation may be considered as a combination of a physical process, SE emission from a specimen, and of an instrumental process, SE detection. In this field, the abundant literature often reflects this sharing with, on the one hand, much work and from a long time on theory and experiments of electron emission from solids [4][5][6][7][8][9] but without attention to SE detection and, on the other , excellent research articles dealing with many important aspects of SE detection [10][11][12][13] but often postulating an isotropic or a Lambert (cosine) angular SE emission from the specimen or dealing with yield curves, d ¼ f(E1), restricted to an approximate sketch without any attention to specimen composition.…”
Section: Introductionmentioning
confidence: 99%